Fibrinogen αC domain: Its importance in physiopathology - Soria, Jeannette (Res Pract Thromb Haemost, 2019)
ESSENTIALS: The C‐terminal domain of the fibrinogen α chain (αC domain) is implicated in different severe diseases via clotting abnormalities or amyloid deposits. Certain anomalies of the fibrinogen molecule lead to amyloid deposits in the kidney, inducing renal insufficiency. In contrast, in Alzheimer's disease, fibrinogen is normal, but due to an inflammatory process, fibrinogen crosses into the brain and interacts with Aβ, leading to formation of pathological deposits. ABSTRACT: Fibrinogen, involved in coagulation, is a soluble protein composed of two sets of disulfide‐bridged Aα, Bβ, and γ‐chains. In this review, we present the clinical implications of the αC domain of the molecule in Alzheimer's disease, hereditary renal amyloidosis and a number of thrombotic and hemorrhagic disorders. In Alzheimer's disease, amyloid beta peptide (Aβ) is increased and binds to the αC domain of normal fibrinogen, triggering increased fibrin(ogen) deposition in patients’ brain parenchyma. In hereditary renal amyloidosis, fibrinogen is abnormal, with mutations located in the fibrinogen αC domain. The mutant αC domain derived from fibrinogen degradation folds incorrectly so that, in time, aggregates form, leading to amyloid deposits in the kidneys. In these patients, no thrombotic tendency has been observed. Abnormal fibrinogens with either a point mutation in the αC domain or a frameshift mutation resulting in absence of a part of the αC domain are often associated with either thrombotic events or bleeding. Mutation of an amino acid into cysteine (as in fibrinogens Dusart and Caracas V) or a frameshift mutation yielding an unpaired cysteine in the αC domain is often responsible for thrombotic events. Covalent binding of albumin to the unpaired cysteine via a disulphide bridge leads to decreased accessibility to the fibrinolytic enzymes, hence formation of poorly degradable fibrin clots, which explains the high incidence of thrombosis. In contrast, anomalies due to a frameshift mutation in the αC connector of the molecule, provoking deletion of a great part of the αC domain, are associated with bleeding.